Sacrifice in Religious Experience. - Albert I. Baumgartner (Editor) (Numen Book Series, 2002)
This book presents revised papers delivered at the 1998 and 1999 Taubes Minerva Center for Religious Anthropology conferences. The papers from the 1998 conference discuss the role of sacrifice in religious experience from a comparative perspective. Those from the second conference examine alternatives to sacrifice. The first theme has been much elaborated in recent scholarship, and the essays here participate in that on-going inquiry. The second theme has been less explored, and the goal of this volume is to stimulate examination of the topic by offering a set of test cases. In both sections of the volume a wide variety of religious traditions are considered. The essays show that in spite of the inclination we may sometimes have to consider sacrifice part of the idolatrous past, long overcome, it remains a persistent and meaningful part of religious experience.